Association Between Body Composition Characteristics and Pulmonary Function Parameters in Young Adults of Shaheed Benazirabad District - Hajira Naila; Zulfiqar Ali Laghari (Pakistan Journal of Medicine and Dentistry)
Background: Obesity is a significant global health issue linked to increased risks of respiratory diseases. This study examines the association between body composition metrics, such as Body Mass Index (BMI) and Waist-to-Hip Ratio (WHR), and lung function in adults aged 20-40 years.